The Effect of Perceived Ease of Use and Perceived Enjoyment on Customer Trust and Loyalty in Online Food Delivery Service - Kurniawan, Shelvy; Tankoma, Alodia (Binus Business Review, 2023)
Competition in the online food delivery industry is getting tougher. Hence, companies in the industry must increase customer trust and loyalty to continue to compete. Factors expected to increase trust and loyalty are perceived ease of use and enjoyment. The research aimed to determine whether there is an influence between perceived ease of use and enjoyment on customer loyalty in the online food delivery service industry in Indonesia, with trust as a mediating variable. The research applied a Â quantitative method, using SEM with WarpPLS 7.0 software. In addition, the unit of analysis was the users of online food delivery services in various cities in Indonesia with purposive sampling. Using online questionnaires, the research obtained 215 participants. Then, data analysis was done by testing the inner and outer models. The analysis results show an influence between perceived ease of use and perceived enjoyment on customer loyalty, with trust as an intervention variable. All the relationships are found to be positive. Perceived ease of use and perceived enjoyment have a positive and significant effect on the trust of online food delivery service users in Indonesia. Similarly, perceived ease of use and perceived enjoyment affect customer loyalty of online food delivery service users in Indonesia positively and significantly. Last, trust positively and significantly influences customer loyalty of online food delivery service users in Indonesia.